Vulnerability modeling and assessment in urban rail transit system - Chen, Hongyu (Nanyang Technological University, 2022)
As a large-scale, high capacity, high efficiency, and sustainable transportation infrastructure, the urban rail transit system gets increasing attention from various countries and regions. A mature urban rail transit system is able to provide effective transportation service for huge passenger volumes as well as emission reduction, which plays an important role in reducing the urban transportation pressure. These properties, however, also contribute to the high difficulty in managing this complicated, large-scale, and highly interdependent system to ensure the stability of the urban rail transit operation. The motivation of this research is to provide a comprehensive vulnerability assessment of urban rail transit that is applicable and effective in practical application, which considers the causality of the system, the dynamic development of the system, and the randomness and uncertainty. This research contributes to the understanding of the static causality relationship in the vulnerability of the urban rail transit system, the improvement of vulnerability assessment of the urban rail transit network structure that considers the instant response to the attack, the long-term evolutional dynamic of the vulnerability of the urban rail transit system, and the knowledge of vulnerability assessment of urban rail transit under the extreme circumstances. This thesis mainly provides the vulnerability assessment for urban rail transit systems from four aspects: (1) To understand and prevent disasters during the urban rail transit operation, a hybrid approach is developed based on the disaster chain mechanism and complex network. The developed approach is able to model and assess the vulnerability of both the disaster events and the whole disaster network in the urban rail transit system and provides a simulation analysis to develop further management strategies; (2) To understand the vulnerability of the line structure of the urban rail transit system with consideration of the instant subsequent condition of the network after the attack, a holistic approach is developed by integrating the complex network theory and cascade failure theory. This method can reasonably simulate the failure of the urban rail transit system to provide a more reliable vulnerability assessment, which could provide management suggestions and support potential scheme selection. (3) To study the long-term dynamics of the vulnerability of the urban rail transit operation that make a further effort on the comprehensive vulnerability development in the life cycle, an evolutional approach is developed that integrates system dynamics and Monte Carlos simulation. The proposed method is able to simulate the long-term tendency of the urban rail transit system and support identifying the important factors to improve long-term vulnerability management. (4) In order to evaluate the vulnerability of the urban rail transit under extreme disasters like rainstorm conditions and improve the vulnerability management in the paroxysmal extreme circumstances with randomness and uncertainty, a holistic approach that combines the cloud model theory and evidential reasoning algorism is developed. The proposed method enables to conduct of a reliable vulnerability assessment of the urban rail transit under rainstorm conditions, which supports the safety and operation management of the urban rail transit. To sum up, the research contributes to (a) the state of the knowledge by developing novel frameworks and methods for vulnerability modeling with weighted complex network and disaster chain mechanism, vulnerability assessment with topological structure and cascade failure effects, long-term evolutional dynamic with system dynamic and Monte Carlos, and vulnerability assessment under extreme disaster with cloud model and evidential reasoning; (b) the state of practice by providing insights into a better understanding of the transmission, spread, control, and prevention of disaster events in the urban rail transit system for disaster risk reduction; the development of cascade failure and the important station identification in the urban rail transit line structure; the long-term dynamic and interaction of the factors for long-term performance improvement of the urban rail transit operation system; and the rainstorm-related factors and relative importance and interrelationship for vulnerability assessment and management improvement.